ANALISIS KESELAMATAN DAN KESEHATAN KERJA (K3) DENGAN METODE JOB SAFETY ANALYSIS (JSA): Proyek Pekerjaan Perkuatan Tebing Sungai dan Pengendalian Banjir Kec. Bolaang Uki, Kab. Bolaang Mongondow Selatan - Lukas V. Rumagit; Yessy C.S. Pandeiroth; Shirly S. Lumeno, (Sustainable Construction (SUSCON), 2024)
Work accidents on construction projects are influenced by the unique characteristics of the project, workers, equipment, materials, and work methods used, as well as weather factors. Environmental issues around the project site often threaten public safety and can damage the environment. The riverbank reinforcement project is considered important for flood mitigation and maintaining a sustainable environment. This study aims to analyze Occupational Health and Safety (OHS) in the riverbank reinforcement and flood control project in Bolaang Uki District, South Bolaang Mongondow Regency, using the Job Safety Analysis (JSA) method to identify hazards, plan preventive actions, and improve OHS. This research is descriptive with an AS/NZS 4360:2004 risk management approach. The analysis indicates that project work involves numerous safety risks, necessitating good OHS management to avoid accidents. Medium-risk tasks include the use of chemicals, vegetation cutting, and environmental management. High-risk tasks involve cutting and drilling cliffs, using heavy equipment, cutting or digging tools, working in water or wet areas, slips, electric shock, and exposure to smoke or dust. Very high-risk tasks are caused by extreme weather conditions. Hazard control efforts include the use of personal protective equipment, provision of standard procedures, and safety certification. Communication aspects are carried out through safety mornings, meetings, toolbox meetings, and regular maintenance of work equipment. Intensive education for workers on implementation methods and OHS plans is necessary to reduce errors and increase knowledge. Serious handling of high to low-risk stages is required. The application of rewards and punishments in project OHS management, provision of personal protective equipment, safety talk briefings, safety inductions, safety patrols, evaluation meetings, and proper organization of tools are highly recommended.